ENHANCEMENT OF AGRICULTURAL KNOWLEDGE WITH BANANA CULTIVATION - Galuh Jati Siwi; Ayu Oktafia; Trimo Laksono; Karmelina Ratnasari; Ainun Safitri; Dewi Amrih (Universitas Djuanda Bogor, 2023)
Youth organization IMKA 08 is a forum for youth activities in Kalidadap II Hamlet, RT 08, which is located in Imogiri Districts, Bantul Regency. Together between IMKA 08 and Universitas PGRI Yogyakarta students as a community service team carried out counseling and training activities on intercropping banana and ginger cultivation. In addition to increasing agricultural knowledge about banana and ginger cultivation, this activity can motivate youth groups and local residents to love agriculture more and can improve the economy with good agriculture. The cultivation system applied in Kalidadap II Hamlet is the use of the yard around the house to make it more productive by intercropping ginger banana cultivation.